Clinical Application of 810nm Diode Laser and Low Level Laser Therapy for Treating an Endodontic Problem A Case Presentation - Asnaashari, Mohammad; Asnaashari, Nikou (Journal of Lasers in Medical Sciences, 2011)
The standards of endodontics have constantly been raised in the last 25 years by practitioners’ researches and their interest. Most of the scientists believe the recent developments and the use of lasers as the most exciting achievement in endodontic treatment. Nowadays, lasers are being used in endodontics to improve the prognosis of the root-filled teeth. The Implement of suitable wavelengths, together with conventional methods, can effectively sterilize the canal, dentin and periapical regions. This article describes a successful treatment of an endodontic case using 810nm diode laser and low Level Laser and sixteen months follow-up to improve healling of the edema.